Blockchain Data Analytics: A Review: Rabia Aslam Khan, Muhammad Bilal But, Sabreena Nawaz - Rabia Aslam Khan; Muhammad Bilal But; Sabreena Nawaz (International Journal for Electronic Crime Investigation, 2023)
Blockchain technology has emerged as a transformative force with widespread applications across various industries. In particular, the analysis of blockchain data has become crucial for crypto businesses and financial institutions seeking to protect transactions from illicit activities, minimize the risk of financial crimes, and ensure compliance with regulations. This paper presents a comprehensive review of blockchain data analytics, focusing on its significance in these domains. The paper examines the advancements and possibilities in blockchain data analytics, shedding light on their transformative potential. It provides an overview of the techniques and tools used for analyzing blockchain data, including transaction tracing, pattern recognition, and anomaly detection. Moreover, it explores the challenges and opportunities associated with blockchain data analytics, such as scalability, privacy concerns, and regulatory frameworks.